Impact of Intrinsic Factors on the Insertion and Permanence of Low-Income Students in Public Universities in 2024 - Loiza, Marco Hernán Pantigozo; Ruíz, Cleidy Sofía Farfán; Salazar, César Augusto E. Lévano; Legua, Fernando Eduardo Cano; Camacho, Dennis Helmle; Ccolque, José Yudberto Vilca; Masías, Marcos Polido (Journal of Posthumanism, 2024)
The development of early childhood is influenced by a multitude of factors, including the psychological resources of caregivers and the socioeconomic conditions of the family environment. The present study sought to examine the correlation between the intrinsic factors of mothers—including levels of self-esteem, anxiety, and perception of the maternal role—and low socioeconomic resources, in the context of the development of cognitive and affective skills in children aged 0 to 2 years. A quantitative correlational methodology was employed, with a sample of 120 mothers from marginal urban sectors. The findings indicated a substantial correlation between diminished maternal self-esteem and constrained affective development in offspring, along with an association between elevated anxiety levels and challenges in the mother-child bond. Conversely, the presence of poverty conditions exhibited a modulatory effect on this relationship. The present findings underscore the necessity of formulating psychosocial interventions that fortify mothers’ emotional resources, particularly in contexts characterized by vulnerability, as a strategy to promote comprehensive child development from the earliest stages of life.